Problems of computer-aided assessment of mathematical knowledge - Vajda, István (Teaching Mathematics and Computer Science, 2013)
Although conventional written and oral exams are dominant in assessment nowadays, computer-aided assessment is developing dynamically. There are several assessment systems, but most of them evaluate only multiple choice questions and even the most sophisticated ones cannot follow the process of thinking of students in detail. Why is it? In this article I will analyse the difficulties of the implementation of assessment system focused primarily on mathematics questions and present some of my experience related to the eMax system, developed at Óbuda University.